2020
DOI: 10.1016/j.jsv.2020.115360
|View full text |Cite
|
Sign up to set email alerts
|

Backside delamination detection in composites through local defect resonance induced nonlinear source behavior

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In addition, the plate with BVID is covered with removable reflective tape (3M™ Scotchlite™ 680CRE10). This was required to be able to detect the nonlinear vibrational components which are of low J o u r n a l P r e -p r o o f amplitude [23,37,38]. In both cases, the propagation of the fundamental anti-symmetric Lamb mode (A 0 ), which has a dominant out-of-plane surface velocity response, is investigated.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the plate with BVID is covered with removable reflective tape (3M™ Scotchlite™ 680CRE10). This was required to be able to detect the nonlinear vibrational components which are of low J o u r n a l P r e -p r o o f amplitude [23,37,38]. In both cases, the propagation of the fundamental anti-symmetric Lamb mode (A 0 ), which has a dominant out-of-plane surface velocity response, is investigated.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…One speaks about nonlinear elastic wave spectroscopy (NEWS) [24][25][26][27][28][29][30] or nonlinear elastic wave modulation spectroscopy (NEWMS) [31][32][33][34][35][36], when there is a single excitation or when there are multiple excitation signals, respectively. Very recently, the current authors used J o u r n a l P r e -p r o o f (numerical as well as experimental) NEWS to show that the nonlinear response at the defect can be used for the detection of shallow damages and, more important, deep backside delaminations [37,38]. It was observed that defects act as secondary sources of higher harmonic vibrational components which can be measured at a distance from the defect's location.…”
Section: Introductionmentioning
confidence: 99%
“…However, an increased activity at the defect is seen in both the second and the third higher harmonic components (Figure 5g,h, respectively). The efficient generation of nonlinear components at the deep defect is related to LDR of the thin material section between the delamination and the backside [34].…”
Section: Defect-to-background Ratio and Local Defect Resonancementioning
confidence: 99%
“…Current authors showed that a backside delamination (i.e. defect's depth > 80% of the sample's thickness) acts as a secondary source of higher harmonics when the excitation frequency matches the defect's backside LDR frequency [40]. In order to increase the nonlinear response at the defect, a second excitation source can be added.…”
Section: Introductionmentioning
confidence: 99%